Opportunities and Student Responses to Audio Visual-Based Learning Media for Learning in Vocational High Schools - Widya Rahma Wati; Sariyatun; Sudiyanto (ELITE Association Indonesia, 2023)
ABSTRACT This study aims to describe student responses to the opportunity to use audio-visual-based learning media for learning fashion. This research method is a descriptive qualitative method. The research subjects consisted of 20 students of vocational high school and 1 teacher of fashion. Data were collected using non-test techniques, namely observations and questionnaires with the instruments consisting of questionnaire items and Observation Sheets. The results of the data obtained from this study will be analyzed descriptively and for the questionnaire will be analyzed using percentages. The results of the study identified that so far teachers have only used presentation-based learning media, the learning method used is dominated by the lecture and demonstration method, which then causes students to tend to be less motivated and this can be seen from the results of the questionnaire distributed to students. In fact, the student response to the development of an audio-visual-based learning media innovation is quite high, so that through this research it appears that the audio-visual-based learning media is large enough to be developed and applied in the hope of facilitating practical learning in vocational high schools, especially material on Clothing. Keywords: Learning Media, Audio Visual, Clothing, Vocational High School